A novel approach to the determination of the pyruvate and acetate distribution in xanthan. (February 2015) - Abbaszadeh, A.; Lad, M.; Janin, M.; Morris, G.A.; MacNaughtan, W.; Sworn, G.; Foster, T.J.
Abstract: The present work demonstrates a quantitative relation between the physical properties of the order disorder transition in xanthan, such as transition temperature and modulus, and the acetate and pyruvate content. Models have been constructed which reflect simple linear dependence of transition temperature and the logarithm of the modulus on acetate, pyruvate, xanthan and salt concentration. Biphasic transitions in xanthan detected using Differential Scanning Calorimetry (DSC) are proposed to reflect phases containing different acetate and pyruvate levels in each phase. The respective acetate and pyruvate contents in these phases have been estimated. 13 C Cross Polarisation Magic Angle Spinning (CPMAS) Nuclear Magnetic Resonance measurements further suggest that the distribution of functional groups measured in solution is reflected in a distribution of environments in solid powders. This could take the form of heterogeneity along an individual chain (intra-chain heterogeneity) or uniform but different levels of functional groups in individual chains (inter-chain heterogeneity). Support for the intra-chain proposal or "blocky" distribution is provided by samples which have been reported to exhibit different transition temperatures despite having apparently the same overall acetate and pyruvate content. This is ascribed to the values of transition temperature being different along an individual chain. Graphical abstract: Highlights: Investigation of a series of xanthans having well defined acetate and pyruvate content. Models of the effect of pyruvate, acetate, salt and xanthan concentration on modulus and transition temperature. Biphasic transitions in DSC due to phases containing different concentrations of both acetate and pyruvate. Acetate and pyruvate methyl peaks in solid state NMR traces related to local environments. Complex aspects of acetate and pyruvate distribution proposed from literature reports and present measurements.